Application of Computer Database System in Information Management - Hu, Kai (Applied Mechanics and Materials, 2014)
This paper analyzes the application of computer database system in information management and proposes the related countermeasure describes. With the continuous development of society, the application of network technology in people's lives is more and more widely, information management are implemented in various enterprises, and computer network is used for data collection and collation.